Polymethoxyflavones: an updated review on pharmacological properties and underlying molecular mechanisms - Zarina Mushtaq; Mahwish Aslam; Muhammad Imran; Mohamed A. Abdelgawad; Farhan Saeed; Tara Khursheed; Maryam Umar; Waleed Al Abdulmonem; Ahmed H. Al Ghorab; Suliman A. Alsagaby; Tabussam Tufail; Muhammad Ahtisham Raza; et al. (International Journal of Food Properties, 2023)
Polymethoxyflavones (PMFs) are dietary bioactive phytochemicals, naturally present in all forms of citrus or plants. For this updated review, the specialized databases of PubMed and Web of Science were researched using keywords such as “polymethoxy flavones,” “pharmacology,” “molecular mechanisms,” “signaling pathways,” and “therapeutic applications.” The most prominent citrus PMFs with proven pharmacological effects are tangeretin, nobiletin, 5′-demethylnobiletin, tetramethyl-o-scutellarein, pentamethoxyflavone, tetramethyl-o-isoscutellarein, and sinensetine. The results of in vivo and in vitro preclinical studies of PMFs have highlighted molecular mechanisms and signaling pathways for anti-inflammatory, anti-cancer, chemopreventive, antidiabetic, anti-obesity, hepatoprotective and neuroprotective effects in neurodegenerative diseases. The results of the studies support the traditional effects of PMFs and therefore it is necessary that these natural compounds be further investigated in clinical trials. PMFs should be designed and formulated in nanoformulations that increase their bioavailability and transport them precisely to the target in order to increase their therapeutic effects.